Cannabinoid type 1 receptor-containing axons innervate NPY/AgRP neurons in the mouse arcuate nucleus - Yury M. Morozov; Marco Koch; Pasko Rakic; Tamas L. Horvath (Elsevier, 2017)
Objectives: Phytocannabinoids, such as THC and endocannabinoids, are well known to promote feeding behavior and to control energy metabolism through cannabinoid type 1 receptors (CB1R). However, the underlying mechanisms are not fully understood. Generally, cannabinoid-conducted retrograde dis-inhibition of hunger-promoting neurons has been suggested to promote food intake, but so far it has not been demonstrated due to technical limitations. Methods: We applied immunohistochemical labeling of CB1R for light microscopy and electron microscopy combined with three-dimensional reconstruction from serial sections in CB1R-expressing and CB1R-null mice, which served as a negative control. Hunger-promoting neurons expressing Agouti-related protein and neuropeptide Y (AgRP/NPY) in the hypothalamic arcuate nucleus were identified in NPY-GFP and NPY-hrGFP mice. Results: Using three-dimensional reconstruction from serial sections we demonstrated numerous discontinuous segments of anti-CB1R labeling in the synaptic boutons and axonal shafts in the arcuate nucleus. We observed CB1R in the symmetric, presumed GABAergic, synaptic boutons innervating AgRP/NPY neurons. We also detected CB1R-containing axons producing symmetric and asymmetric synapses onto AgRP/NPY-negative neurons. Furthermore, we identified CB1R in close apposition to the endocannabinoid (2-arachidonoylglycerol)-synthesizing enzyme diacylglycerol lipase-alpha at AgRP/NPY neurons. Conclusions: Our immunohistochemical and ultrastructural study demonstrates the morphological substrate for cannabinoid-conducted feeding behavior via retrograde dis-inhibition of hunger-promoting AgRP/NPY neurons. Keywords: Hypothalamus, Arcuate nucleus, Agouti-related protein, Neuropeptide Y, Electron microscopy, 3D reconstruction